Zinc ion battery electrolyte containing additives, preparation method thereof, and zinc ion battery

By adding specific additives to the electrolyte of the zinc ion battery, an inorganic solid protective film is formed, which solves the problems of zinc dendrites growth, electrolyte decomposition and cathode material dissolution during the charging and discharging of zinc ion batteries, and improves the cycle stability and service life of the battery.

CN114665153BActive Publication Date: 2025-03-25ZHEJIANG GOLDEN FEATHER NEW ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210271896.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-21
Publication Date
2025-03-25
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

During the charging and discharging process of zinc ion batteries, zinc dendrites growth, electrolyte decomposition and cathode material dissolution, resulting in poor circulation stability.

Method used

Add specific additives, such as molybdate, methanesulfonate or organic compounds containing S and F substituted groups to the electrolyte of zinc ion batteries. These additives will produce precipitates on the surface of the electrode material as the pH increases, forming an inorganic solid protective film to prevent the electrode material from contacting the electrolyte directly.

Benefits of technology

By forming an inorganic solid protective film, the electrode material is effectively prevented from being eroded and dissolved by the electrolyte, and the cycle stability and service life of the zinc ion battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114665153B_ABST
    Figure CN114665153B_ABST
Patent Text Reader

Abstract

The present invention discloses an additive-containing zinc ion battery electrolyte, a preparation method thereof, and a zinc ion battery. The electrolyte of the present invention comprises an additive, an electrolyte salt, and a solvent; the additive is at least one of an oxygen-containing acid salt. The electrolyte of the present invention is added with an additive, and the additive will produce a precipitate as the pH value of the electrolyte increases, and the precipitate does not dissolve with the change of pH. When it is applied to a battery, based on the change of environmental pH at the contact interface between the electrode material and the electrolyte, an inorganic solid protective film can be formed on the surface of the electrode material to prevent the material from directly contacting the electrolyte, thereby avoiding the material from being corroded and dissolved by the electrolyte, and improving the cycle stability of the positive and negative electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of zinc ion batteries, in particular to an additive-containing zinc ion battery electrolyte, a preparation method thereof and a zinc ion battery. Background Art

[0002] Zinc-ion battery is a battery system with metallic zinc as the negative electrode material and neutral or slightly acidic aqueous electrolyte. It has high energy density, is inherently non-flammable and low-cost, and is very suitable for large-scale energy storage and distributed energy storage. However, there are still some problems to be solved in zinc-ion batteries, such as zinc dendrite growth, electrolyte decomposition, and dissolution of positive electrode materials. The main reason for these problems is that the positive and negative electrode materials are in direct contact with the aqueous electrolyte.

[0003] In order to achieve better application effects of zinc ion batteries, it is a common solution to improve the electrolyte. For example, patent CN112652825A adds fluoride salts to the electrolyte. Fluoride salts can form insoluble fluorides on the zinc surface to protect the zinc negative electrode, but it only improves the electrochemical performance of the zinc negative electrode. The positive electrode materials used in zinc ion batteries, such as manganese-based compounds, vanadium-based compounds or Prussian blue compounds, will dissolve to varying degrees in the electrolyte, destroying the original structure of the material, resulting in a decrease in the coulomb efficiency of the battery and a decrease in the discharge capacity in the later stage of the cycle. Therefore, the positive electrode material also needs to be protected to improve the cycle performance of the battery. Summary of the invention

[0004] In view of the limitations of the above-mentioned prior art, the present invention provides an additive-containing zinc ion battery electrolyte, a preparation method thereof, and a zinc ion battery. An additive is added to the electrolyte of the present invention, and the additive will produce a precipitate as the pH value of the electrolyte increases, and the precipitate does not dissolve with the change of pH. When it is applied to a battery, polarization occurs on the surface of the positive and negative electrode materials during the charge and discharge process to produce a local pH change, so that the additive component generates a precipitate in situ on the surface of the electrode material, thereby forming an inorganic solid protective film on the surface of the electrode material, preventing the electrode material from directly contacting the electrolyte, thereby avoiding the electrode material from being eroded and dissolved by the electrolyte, and improving the cycle stability of the positive and negative electrode materials.

[0005] One of the purposes of the present invention is to provide an additive-containing zinc ion battery electrolyte, wherein the electrolyte comprises the additive, an electrolyte salt and a solvent;

[0006] The additive will produce precipitates as the pH value of the electrolyte increases, and the precipitates will not dissolve with the change of pH; the additive is at least one of an oxygen-containing acid salt or an organic compound containing S, F substitution groups.

[0007] Preferably, the oxygen-containing acid salt is selected from at least one of molybdate, methanesulfonate or sulfate.

[0008] Preferably, the concentration of the additive in the electrolyte is 0.05-0.5 mol / L.

[0009] In the present invention, the content of the additive in the electrolyte is not higher than 0.5 mol / L, otherwise the excessive precipitate formed will block the reaction area of ​​the positive electrode and the negative electrode, reducing the battery performance; the content of the additive in the electrolyte is not lower than 0.05 mol / L, otherwise an effective protective layer cannot be formed and the effect is not obvious.

[0010] The molybdate includes a soluble salt formed by a molybdate radical and an alkali metal or an ammonium radical, including but not limited to at least one of sodium molybdate, ammonium molybdate or potassium molybdate;

[0011] The methanesulfonate includes a soluble salt formed by bismuth ions, tin ions and methanesulfonic acid, including but not limited to at least one of bismuth methanesulfonate or tin methanesulfonate;

[0012] The sulfate includes sulfates of titanium ions and chromium ions, including but not limited to at least one of titanium sulfate or chromium sulfate;

[0013] The organic compound containing S and F substituent groups includes but is not limited to at least one of thioformamide, thioacetamide, fluoroethylene carbonate or fluoroacetic acid.

[0014] Preferably, the initial pH value of the electrolyte is ≤3, preferably the initial pH value of the electrolyte is ≤2, and more preferably the initial pH value of the electrolyte is ≤1.5.

[0015] In the present invention, additives are an important part of whether the electrolyte can produce an optimized effect. The additives are added when the pH value of the electrolyte is relatively low and are in a completely dissolved state. When the pH value of the electrolyte gradually increases due to environmental changes and other factors, the additives will undergo a chemical reaction to produce a precipitate, and the precipitate will not dissolve with changes in pH.

[0016] Different additives have different chemical reactions and precipitation types when forming precipitation. For molybdate additives such as sodium molybdate, zinc molybdate and molybdenum trioxide precipitation will be formed when the pH value of the electrolyte increases; for methanesulfonates such as bismuth methanesulfonate, bismuth oxide precipitation will be formed when the pH value of the electrolyte increases; for sulfates such as titanium sulfate, titanium oxide precipitation will be formed when the pH value of the electrolyte increases; for organic compounds containing S or F, such as thioacetamide, when the pH value of the electrolyte increases, the hydrogen sulfide generated by its hydrolysis will encounter Zn in the solution. 2+ZnS precipitates will be formed. Since the pH change is limited to the surface of the electrode material, these precipitates will adhere to the surface of the particles to form a protective film.

[0017] There are two possible reasons why the precipitate no longer dissolves again with changes in the environmental pH after it is generated. One is that the electrolyte is in a supersaturated state when dissolved, and only a moderate change in temperature and pH will cause a dissolution equilibrium disorder to produce a precipitate. Another reason is that the precipitate recrystallizes after it is generated, and the solubility product is smaller, so the previous solution environment can no longer dissolve it.

[0018] In the present invention, the electrolyte salt is an electrolyte salt commonly used in zinc ion batteries; preferably, the electrolyte salt is selected from soluble zinc salts; including but not limited to the soluble zinc salts selected from one or more of zinc sulfate, zinc methanesulfonate, zinc trifluoromethanesulfonate or zinc nitrate;

[0019] The concentration of the electrolyte salt is 0.5 to 3 mol / L;

[0020] Preferably, the electrolyte salt also includes a soluble salt formed by an acid anion and an alkali metal or ammonium cation;

[0021] The acid anions include one or more of sulfate ions, methanesulfonate ions, trifluoromethanesulfonate ions or nitrate ions, and the concentration of the acid anions is preferably 0.5 to 6 mol / L;

[0022] The alkali metal or ammonium cation includes one or more of lithium ion, sodium ion, potassium ion and ammonium ion. Preferably, the concentration of the alkali metal or ammonium cation is 0.1-3 mol / L.

[0023] The electrolyte salt of the present invention includes but is not limited to the electrolyte salt composed of the above-mentioned anions and cations. Since there are too many types of electrolyte salts formed by the above-mentioned anions and cations, they are not described one by one here.

[0024] Preferably, the solvent is selected from water or a mixed solvent of water / organic solvent;

[0025] Preferably, the organic solvent is one or more of DMSO, formamide, sulfolane, acetonitrile or DMF;

[0026] Preferably, the mass proportion of the organic solvent in the mixed solution is 5wt% to 40wt%;

[0027] More preferably, the solvent corresponding to the mesylate additive is a mixed solvent of water / DMSO; one of the effects of the organic solvent is that it can produce a complex with the ions in the additive to keep it in a stable state in the electrolyte. For example, when using bismuth mesylate additive, the solvent needs to be a mixed solution of water and DMSO because DMSO and Bi 3+ A relatively stable complex is formed, and the bismuth ion is dissolved in the electrolyte in the form of a complex.

[0028] The second object of the present invention is to provide a method for preparing the zinc ion electrolyte described in the first object of the present invention, wherein an electrolyte salt and an additive are added to the solvent in proportion, mixed and dissolved, to obtain a clear electrolyte;

[0029] Before adding the additive, after adding the additive and until the electrolyte is prepared, the pH value of the solution system is kept ≤ 3, so that the additive can remain dissolved in the electrolyte. In the present invention, the pH value of the electrolyte can be adjusted by a commonly used pH adjuster.

[0030] The third object of the present invention is to provide a zinc ion battery containing the zinc ion electrolyte described in one of the objects of the present invention, wherein the zinc ion battery comprises a negative electrode, a positive electrode and an electrolyte;

[0031] The negative electrode includes metallic zinc;

[0032] In the present invention, the positive electrode material can be any commonly used material. Preferably, the positive electrode comprises a manganese-based compound, a vanadium-based compound or a Prussian blue compound.

[0033] The zinc ion battery also includes a separator, a current collector and a battery case.

[0034] Since the main component of the solvent in the electrolyte of the present invention is water, the surface of the particles of the positive and negative electrode materials inside the battery will be affected by polarization during the charge and discharge process, causing local pH changes, causing the pH to increase or decrease. When the local pH increases, the additive forms a precipitate in the region in situ, and the precipitate is therefore covered on the surface of the positive and negative electrode materials to form a protective film, preventing the positive and negative electrode active materials from directly contacting the electrolyte, thereby avoiding the active materials from being eroded and dissolved by the electrolyte, and improving their cycle stability. It can be seen that the additive in the electrolyte of the present invention can produce an effect in both the positive and negative electrodes of the battery, and can further improve the overall cycle stability of the battery.

[0035] Preferably, the manganese-based compound comprises manganese oxide or manganate;

[0036] Preferably, the manganese oxide includes but is not limited to at least one of manganese monoxide, manganese dioxide, manganese trioxide or manganese tetraoxide;

[0037] Preferably, the manganate includes but is not limited to at least one of lithium manganate, zinc manganate, sodium manganate or calcium manganate;

[0038] The vanadium-based compounds include but are not limited to vanadium oxides or vanadium oxyacid salts;

[0039] Preferably, the vanadium oxide includes but is not limited to VO 2 、V 6 O 13 or V 2 O 5 At least one of;

[0040] Preferably, the vanadium oxyacid salt includes but is not limited to Zn 0.25 V 2 O 5 、Na 3 V 2 (PO 4 ) 3 、ZnV 2 O 4 MgV 2 O 4 At least one of;

[0041] The Prussian blue compounds include but are not limited to K 2 MnFe(CN) 6 , K 2 NiFe(CN) 6 , K 3 Fe 2 (CN) 6 At least one of .

[0042] Compared with the prior art, the present invention has the following advantages and outstanding effects:

[0043] An additive is added to the electrolyte of the present invention, and the additive can form an inorganic solid protective film on the surface of the positive and negative electrode materials, thereby improving the stability of the battery material in the aqueous electrolyte. The additive can produce a precipitate as the pH value of the electrolyte environment increases. After the precipitate is formed, it no longer dissolves with the change of pH and exists stably in the electrolyte. When it is applied to a battery, the local pH increase of the electrolyte causes the additive to form a precipitate in situ in the area. The precipitate forms a protective film on the surface of the positive or negative electrode material to prevent the material from directly contacting the electrolyte, thereby avoiding the active material from being eroded and dissolved by the electrolyte, improving its cycle stability, and extending the service life of the battery, thereby effectively solving the problem of poor cycle stability performance of zinc ion batteries.

[0044] The additive added to the electrolyte of the present invention can produce effects in both the positive electrode and the negative electrode of the battery. Compared with the existing common additives, the electrolyte additive of the present invention has a wider range of effects and better effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 1 is a cycle-discharge specific capacity / efficiency diagram of the battery of Example 1 of the present invention;

[0046] Figure 2 This is a scanning electron microscope image of the positive electrode material of Example 1 of the present invention after 20 cycles;

[0047] Figure 3 This is an optical photograph of the negative electrode material of Example 1 of the present invention after 20 cycles;

[0048] Figure 4 1 is a cycle-discharge specific capacity / efficiency diagram of the battery of Comparative Example 1 of the present invention;

[0049] Figure 5 This is a scanning electron microscope image of the positive electrode material of Comparative Example 1 of the present invention after 20 cycles;

[0050] Figure 6 This is an optical photograph of the negative electrode material of Comparative Example 1 of the present invention after 20 cycles. DETAILED DESCRIPTION

[0051] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0052] The raw materials used in the examples can be purchased directly;

[0053] The reactions in the examples were all carried out at room temperature.

[0054] Example 1

[0055] Prepare electrolyte: weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100 ml and add appropriate amount of 98% sulfuric acid to adjust the pH of the solution to 2.8, then dissolve 1.02g sodium molybdate (0.05mol / L) in the solution, mix well, and prepare a colorless clear electrolyte.

[0056] Battery assembly: Grind and clean the surface of the 0.1 mm thick zinc foil and cut The disc is used as the negative electrode; MnO 2 As positive electrode active materials, a certain mass of positive electrode active materials, acetylene black and polyvinylidene fluoride were weighed in a mass ratio of 85:10:5, and the materials were mixed, coated and dried to form electrode sheets, and then cut The disc is used as the positive electrode; take the glass fiber separator and cut The disc is reserved; the negative electrode plate, separator, and positive electrode plate are stacked in order and placed in a 2032-model battery shell, and then a small amount of electrolyte is added to moisten the inside to assemble a 2032-model button battery.

[0057] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.9 V and a rate current of 0.3C.

[0058] Battery performance test results are as follows Figure 1 As shown, the initial discharge specific capacity of the battery is 158.4 mAh / g, the coulombic efficiency of the battery is >99.5% within 100 cycles, the gram capacity after 100 cycles is 155.3 mAh / g, and the capacity retention rate after 100 cycles is 98%.

[0059] After 20 cycles, the battery was disassembled, the positive and negative electrodes were taken out, and the residual electrode liquid was washed away with clean water. After being fully dried, the positive electrode was tested by scanning electron microscopy. The test results are as follows: Figure 2 As shown, it can be observed that the electrode surface is covered with a large amount of crystalline substances with good crystallinity. These substances constitute a protective layer for the positive electrode material, reducing the contact area between the material and the electrolyte and preventing it from being corroded by the electrolyte. The negative electrode sheet is observed using an optical imager, and the test results are as follows: Figure 3 As shown, light-colored substances can be seen covering the surface of the negative electrode, indicating that the additive of the present invention can produce the same effect in the negative electrode region, coating the zinc surface with an inorganic film to prevent the zinc electrode from directly contacting the electrolyte. Therefore, from the above results, it can be seen that the additive of the present invention can form an inorganic solid protective film on the surface of both the positive and negative electrode materials, thereby improving the cycle stability of the positive and negative electrode materials, thereby improving the cycle stability of the battery.

[0060] The battery test performance results are shown in Table 1.

[0061] Example 2

[0062] Prepare electrolyte: weigh zinc methanesulfonate and sodium methanesulfonate powder and dissolve them in deionized water to prepare 1 mol / L NaSO 3 CH 3 +1mol / L Zn(CH 3 SO 3 ) 2 Solution, take 100 ml and add an appropriate amount of 98% methanesulfonic acid to adjust the pH of the solution to 3, then weigh 5.15 g (0.25 mol / L) of sodium molybdate and dissolve it in the solution, and finally prepare a clear and light green electrolyte.

[0063] Battery assembly: According to the method of Example 1, wherein the positive electrode material is LiMn 2 O 4 .

[0064] Battery test: The battery performance test is carried out using constant current and constant voltage charge and discharge methods. The charge and discharge voltage range is 0.8V to 1.95V, and the rate current is 0.2C.

[0065] The battery test performance results are shown in Table 1.

[0066] Example 3

[0067] Prepare electrolyte: weigh zinc methanesulfonate powder and dissolve it in deionized water to prepare 2 mol / L Zn(CH 3 SO 3 ) 2 Solution, take 100 ml and add an appropriate amount of 98% methanesulfonic acid to adjust the pH of the solution to 1.5, add 10 vol% DMSO, then weigh 5 g (0.1 mol / L) of bismuth methanesulfonate and dissolve it in the solution, and finally configure it into a colorless and transparent electrolyte.

[0068] Battery assembly: According to the method of Example 1, wherein the positive electrode material is MnO 2 .

[0069] Battery test: The battery performance test was carried out using a constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.9 V and a rate current of 0.3C.

[0070] The battery test performance results are shown in Table 1.

[0071] Example 4

[0072] Prepare electrolyte: Weigh zinc sulfate heptahydrate powder and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100ml and add an appropriate amount of 98% concentrated sulfuric acid, adjust the solution pH to 1, then weigh 4.8g (0.2mol / L) of titanium sulfate and dissolve it in the solution, and finally prepare a colorless and transparent electrolyte.

[0073] Battery assembly: According to the method of Example 1, wherein the positive electrode material is MnO 2 .

[0074] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.95 V and a rate current of 0.2C.

[0075] The battery test performance results are shown in Table 1.

[0076] Example 5

[0077] Prepare electrolyte: Weigh an appropriate amount of zinc methanesulfonate powder and dissolve it in deionized water to prepare 2 mol / L Zn(CH 3 SO 3 ) 2 solution, add an appropriate amount of 98% methanesulfonic acid to adjust the pH of the electrolyte to 1.5, weigh 0.75g (0.1mol / L) of thioacetamide and dissolve it in 100ml of the solution and mix well to prepare an electrolyte.

[0078] Battery assembly: According to the method of Example 1, wherein the positive electrode material is MnO 2 .

[0079] Battery test: The battery performance test was carried out using a constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.9 V and a rate current of 0.3C.

[0080] The battery test performance results are shown in Table 1.

[0081] Example 6

[0082] Prepare electrolyte: weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100 ml and add appropriate amount of 98% sulfuric acid to adjust the pH of the solution to 2.8, then dissolve 4.12 g (0.2 mol / L) of sodium molybdate in the solution, mix well, and prepare a colorless clear electrolyte.

[0083] Battery assembly: According to the method of Example 1, wherein the positive electrode material is VO 2 .

[0084] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.4 to 1.8 V and a rate current of 0.3C.

[0085] The battery test performance results are shown in Table 1.

[0086] Example 7

[0087] Prepare electrolyte: weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100 ml and add appropriate amount of 98% sulfuric acid to adjust the pH of the solution to 2.8, then dissolve 4.12 g (0.2 mol / L) of sodium molybdate in the solution, mix well, and prepare a colorless clear electrolyte.

[0088] Battery assembly: According to the method of Example 1, wherein the positive electrode material is Zn 0.25 V 2 O 5 .

[0089] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.4 to 1.8 V and a rate current of 0.3C.

[0090] The battery test performance results are shown in Table 1.

[0091] Example 8

[0092] Prepare electrolyte: weigh zinc trifluoromethanesulfonate and potassium trifluoromethanesulfonate and dissolve them in deionized water to prepare 1 mol / L ZnSO 3 CF 3 +1mol / L KSO 3 CF 3 Take 100 ml of the solution, add an appropriate amount of 98% trifluoromethanesulfonic acid to adjust the pH of the solution to 2.8, then dissolve 4.12 g (0.2 mol / L) of anhydrous sodium molybdate in the solution, mix well, and prepare a colorless clear electrolyte.

[0093] Battery assembly: According to the method of Example 1, wherein the positive electrode material is K 2 MnFe(CN) 6 .

[0094] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.6 to 1.9 V and a rate current of 0.3C.

[0095] The battery test performance results are shown in Table 1.

[0096] Example 9

[0097] Prepare electrolyte: weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100 ml and add appropriate amount of 98% sulfuric acid to adjust the pH of the solution to 2.8, then dissolve 4.12 g (0.2 mol / L) of anhydrous sodium molybdate in the solution, mix well, and prepare a colorless clear electrolyte.

[0098] Battery assembly: According to the method of Example 1, wherein the positive electrode material is MnO 2 .

[0099] Battery test: The battery performance test was carried out using the constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.9 V and a rate current of 0.3C.

[0100] The battery test performance results are shown in Table 1.

[0101] Example 10

[0102] Prepare electrolyte: weigh zinc sulfate heptahydrate and dissolve it in deionized water to prepare 2 mol / L ZnSO 4 Solution, take 100 ml and add appropriate amount of 98% sulfuric acid to adjust the pH of the solution to 2.8, then dissolve 0.78 g of fluoroacetic acid (0.1 mol / L) in the solution, mix well, and prepare a colorless clear electrolyte.

[0103] Battery assembly: According to the method of Example 1, wherein the positive electrode material is MnO 2 Battery test: The battery performance test was carried out using a constant current charge and discharge method, with a charge and discharge voltage range of 0.8 to 1.9 V and a rate current of 0.3C.

[0104] The battery test performance results are shown in Table 1.

[0105] Comparative Example 1

[0106] The same as Example 1, except that the electrolyte is 2 mol / L ZnSO 4 Solution, pH adjusted to 2.8, contains no additives.

[0107] The battery assembly is basically the same as in Example 1.

[0108] The battery test is basically the same as that in Example 1.

[0109] Battery test performance results are as follows Figure 4 As shown, the initial specific capacity of the battery is 152 mAh / g. Within 100 cycles, it can be seen that the coulombic efficiency is unstable. The coulombic efficiency during 36-43 cycles and 76-86 cycles is less than 95%, indicating that the battery has obvious side reactions in this range, and the discharge specific capacity after 100 cycles is 125 mAh / g, and the capacity retention rate is 83%, which is lower than that of Example 1 of the present invention. In general, the main reason for the low coulombic efficiency of aqueous batteries is the hydrogen evolution side reaction at the negative electrode, and the main reason for the capacity decay is the dissolution and decomposition of the positive electrode material in the electrolyte. By comparing the battery cycle performance of Example 1 of the present invention and Comparative Example 1, it can be found that the additive of the present invention can have a beneficial effect on both the positive electrode material and the negative electrode material, which is reflected in the cycle efficiency and capacity retention rate, and can effectively improve the use effect of the aqueous battery.

[0110] After 20 cycles, the battery was disassembled, the positive and negative electrodes were taken out, and the residual electrode liquid was washed away with clean water. After being fully dried, the positive electrode was tested by scanning electron microscopy. The test results are as follows: Figure 5 As shown in the figure, the active material particles inside the electrode can be seen, and the surface of the particles is not covered with any crystals; the negative electrode is observed using an optical imager, and the test results are as follows Figure 6As shown, due to the short cycle period, the zinc negative electrode has no obvious reaction traces, and the surface is still silver-gray. Since there is no additive that can form precipitates in the electrolyte, it shows the original state of metallic zinc. By disassembling and observing the batteries after the cycles of Example 1 and Comparative Example 1, it can be found that the electrolyte containing additives of the present invention has a very obvious effect on the electrode material, and can form a layer of inorganic solid protective film covering the electrode surface, effectively preventing the material from being corroded by the aqueous electrolyte.

[0111] Comparative Example 2

[0112] It is basically the same as Example 1, except that the addition amount of the additive sodium molybdate is 12.3 g (0.6 mol / L), the solution becomes turbid, and a white precipitate is present.

[0113] The battery test performance results are shown in Table 1.

[0114] Comparative Example 3

[0115] The method is basically the same as Example 1, except that the amount of additive added is 0.12 g (0.005 mol / L). The battery test performance results are shown in Table 1.

[0116] Comparative Example 4

[0117] The method is basically the same as Example 1, except that the concentration of the added additive is 0.5 mol / L sodium fluoride. The battery test performance results are shown in Table 1.

[0118] Comparative Example 5

[0119] The method is basically the same as Example 1, except that the additive added is sodium dihydrogen phosphate, and the added amount is 1.2 g (0.1 mol / L). The battery test performance results are shown in Table 1.

[0120] Table 1

[0121]

[0122] Table 1 lists the coulombic efficiency within 100 cycles and after 100 cycles of the battery of the embodiment of the present invention and the comparative example. Compared with the comparative example, the battery of the embodiment using the electrolyte containing the additive of the present invention shows excellent coulombic efficiency and cycle performance; as in Example 1, sodium molybdate is used as an additive. Due to concentration polarization on the electrode surface during charging and discharging, the concentration of hydroxyl groups at the interface between the electrode piece and the electrolyte increases or decreases, resulting in a local pH change. When the pH on the surface of the electrode material increases, the molybdate radical is hydrolyzed to generate molybdenum trioxide, which is in situ deposited on the surface of the positive and negative electrodes to form a highly crystalline and dense inorganic protective film, thereby effectively alleviating the corrosion of the electrolyte on the positive and negative electrode pieces and improving the battery cycle performance; similarly, the additives used in Examples 2 to 6 are all based on the change of the environmental pH at the interface between the electrode piece and the electrolyte, so that the additives generate precipitates of different components in situ on the surface of the positive and negative electrode pieces to form a protective film to prevent the material from direct contact with the electrolyte, thereby avoiding the material from being corroded and dissolved by the electrolyte and improving its cycle stability.

[0123] Furthermore, the results of Examples 1 to 10 show that the additive-containing electrolyte of the present invention can achieve high coulombic efficiency and high capacity retention rate when adapted to different types of positive electrode materials, and the combination of the additives with different electrolyte salts will not affect the improvement effect on the battery.

[0124] Comparative Example 4 uses fluoride salt as an electrolyte additive, dissolving a certain amount of fluoride ions in the electrolyte. During the charging process, the fluoride ions gather in the negative electrode area to form a zinc fluoride protective film, which can effectively improve the coulomb efficiency of the battery. However, the cycle life of the battery is not as good as that of the fluorine-containing additive in Example 10 of the present invention. This is because its action area is limited to the negative electrode side, and it is difficult to form a zinc fluoride protective film in situ on the surface of the material in the positive electrode area. Similarly, Comparative Example 5 uses phosphate as an electrolyte additive, which can obtain good coulomb efficiency, but the capacity of the battery is low because its main action area is the negative electrode side. In aqueous batteries, effective protection of the positive electrode material can increase the service life of the battery.

[0125] At the same time, too low or too high concentration of additives is not conducive to battery cycle performance. For example, in Comparative Example 2, the additive concentration is too high, which leads to the inability of the additive and the zinc salt to coexist, a large amount of precipitate is generated, the electrolyte ion conductivity is reduced, and the precipitate will further block the diaphragm pores, which is not conducive to ion transmission and battery performance degradation; in Comparative Example 3, the additive concentration is too low, the resulting dense film is relatively thin, and cannot cover the entire active material surface, and cannot effectively prevent the active material from contacting the electrolyte, the coulomb efficiency is low, and the cycle stability is poor. Therefore, the additive of the present invention needs to be within a suitable concentration range to produce an optimization effect.

[0126] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A zinc ion battery electrolyte containing an additive, characterized in that: The electrolyte comprises an additive, an electrolyte salt and a solvent; The additive will produce a precipitate as the pH value of the electrolyte increases, and the precipitate will not dissolve again as the pH value changes; The additive is at least one of oxygen-containing acid salts; the oxygen-containing acid salt is selected from at least one of molybdate, methanesulfonate or sulfate; The molybdate includes at least one of the soluble salts formed by molybdate and alkali metal; The methanesulfonate includes at least one of soluble salts formed by bismuth ions, tin ions and methanesulfonic acid; The sulfate includes at least one of sulfates of titanium ions and chromium ions; The initial pH value of the electrolyte is ≤3.

2. The zinc ion battery electrolyte according to claim 1, wherein: The concentration of the additive in the electrolyte is 0.05-0.5 mol / L.

3. The zinc ion battery electrolyte according to claim 1, wherein: The molybdate is at least one of sodium molybdate or potassium molybdate; The methanesulfonate is at least one of bismuth methanesulfonate or tin methanesulfonate; The sulfate is at least one of titanium sulfate or chromium sulfate.

4. The zinc ion battery electrolyte according to claim 1, wherein: The electrolyte salt is selected from soluble zinc salts; The concentration of the electrolyte salt is 0.5-3 mol / L; The electrolyte salt also includes a soluble salt formed by an acid anion and an alkali metal or ammonium cation; The acid anions include one or more of sulfate ions, methanesulfonate ions, trifluoromethanesulfonate ions or nitrate ions; The alkali metal cations include one or more of lithium ions, sodium ions, and potassium ions.

5. The zinc ion battery electrolyte according to claim 1, wherein: The solvent is selected from water or a mixed solvent of water / organic solvent; The organic solvent is one or more of DMSO, formamide, sulfolane, acetonitrile or DMF; The mass proportion of the organic solvent in the mixed solution is 5wt%~40wt%; The solvent corresponding to the mesylate additive is a mixed solvent of water / DMSO.

6. according to the preparation method of the arbitrary described zinc ion electrolyte of claim 1-5, it is characterized in that: Adding electrolyte salt and additives into the solvent in proportion, mixing and dissolving, and preparing a clear electrolyte; The pH value of the solution system is maintained at ≤3 before, after and until the electrolyte is prepared.

7. A zinc ion battery using the zinc ion electrolyte according to any one of claims 1 to 5, characterized in that: The zinc ion battery comprises a negative electrode, a positive electrode and an electrolyte; The negative electrode includes metallic zinc; The positive electrode includes at least one of a manganese-based compound, a vanadium-based compound or a Prussian blue compound.

8. The zinc ion battery according to claim 7, characterized in that: The manganese-based compound includes manganese oxide or manganate; The manganese oxide is selected from at least one of manganese monoxide, manganese dioxide, manganese trioxide or manganese tetraoxide; The manganate is selected from at least one of lithium manganate, zinc manganate, sodium manganate or calcium manganate; Vanadium-based compounds include vanadium oxides or vanadium oxoates; The vanadium oxide is selected from VO2, V6O 13 or at least one of V2O5; The vanadium oxyacid salt is selected from Zn 0.25 At least one of V2O5, Na3V2(PO4)3, ZnV2O4 or MgV2O4; The Prussian blue compound is selected from at least one of K2MnFe(CN)6, K2NiFe(CN)6 or K3Fe2(CN)6.

Citation Information

Patent Citations

  • High and low temperature performance-considered high-voltage electrolyte and lithium ion battery thereof

    CN109638351A

  • Method for protecting electrode of zinc ion battery

    CN111934033A